Cedência de elementos contaminantes de bentonites ao vinho: contributo para a optimização de uma solução teste - Sousa, Raul Bruno de (2009)
The release of mineral elements from six bentonites to wine and to the test solution established by the OIV was evaluated in order to compare the extraction performance of both solutions.Significant differences between wine and tartaric solution results for 34 mineral elements analyzed by AAS, ETAAS and ICP-MS were observed, suggesting that the extraction solution proposed by the OIV is not suitable for bentonite quality control purposes.